From General to Specific English: A Case Study of NUML - Dar, Maryam (Journal of NELTA, 2011)
The present study was conducted to explore the need for ESP courses in Pakistani universities. The present study scrutinizes the target needs of the students of Advanced English Language Diploma of National Universities of Modern Languages who join the Language Course for occupational purposes. The sample for the study consisted of 40 students, 5 teachers and 5 alumni. The needs, lacks, wants, expectations, preferred style of learning, interest and satisfaction level of students were determined with the help of Needs Analysis using questionnaires, interviews and observation tools. The results indicate low interest and satisfaction level of the students due to the general nature of the Diploma course. This calls for the separate ESP courses for the students who join the English Diploma courses for occupational reasons. Key words: Needs analysis; English for specific purposes; General to specific; NUML; ESP in Pakistan Journal of NELTA Vol. 15 No. 1-2 December 2010 Page: 28-42 Uploaded date: 4 May, 2011 DOI: 10.3126/nelta.v15i1-2.4607